2011
DOI: 10.1108/02610151111183207
|View full text |Cite
|
Sign up to set email alerts
|

A “lesbian advantage”?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Here, we examine additional life transitions as related to desires and intentions of parenthood such as one’s idealization of parenthood, their partner expectations during the transition to parenthood, perceived self-efficacy, and changes in professional and financial resources. In terms of professional intentions, given previous work that suggests a difference between LH women (Wright, 2011), we anticipate finding a similar relationship of lesbian women wanting to work more than heterosexual women. However, given that less work has included samples of BLH women together, we make no confirmatory hypotheses regarding the similarities or differences between BLH women in terms of other constructs of interest such as idealization of parenthood, partner expectations, perceived self-efficacy, and financial considerations.…”
Section: Current Studymentioning
confidence: 80%
See 1 more Smart Citation
“…Here, we examine additional life transitions as related to desires and intentions of parenthood such as one’s idealization of parenthood, their partner expectations during the transition to parenthood, perceived self-efficacy, and changes in professional and financial resources. In terms of professional intentions, given previous work that suggests a difference between LH women (Wright, 2011), we anticipate finding a similar relationship of lesbian women wanting to work more than heterosexual women. However, given that less work has included samples of BLH women together, we make no confirmatory hypotheses regarding the similarities or differences between BLH women in terms of other constructs of interest such as idealization of parenthood, partner expectations, perceived self-efficacy, and financial considerations.…”
Section: Current Studymentioning
confidence: 80%
“…Compared to heterosexual parents, factors such as being older when becoming a parent (Farr & Patterson, 2013a; Stotzer et al, 2014), greater pressure to be financially stable (Hetherington & Orzek, 1989), and the more frequent pursuit of male-dominated careers (e.g., upper-level management; Wright, 2011) all influence how lesbian women navigate career paths. Given the economic strain on bisexual women (Cerf, 2016), these factors may also impact how they envision future parenthood.…”
Section: Professional and Economic Considerationsmentioning
confidence: 99%
“…A number of qualitative studies have looked at what it is like to be a sexual minority in different work environments, including policing (Charles & Arndt, 2013;Hassell & Brandl, 2009), firefighting (Wright, 2008), nursing (Eliason, DeJoseph, Dibble, & Chinn, 2011), accounting (Stenger & Roulet, 2018), academia (Bilimoria & Stewart, 2009;Dozier, 2015;Patridge, Barthelemy, & Rankin, 2014;Taylor & Raeburn, 1995), and engineering (Cech & Waidzunas, 2011;Riley, 2008). Other studies have focused on sectors, including construction and transportation industries (Wright, 2011), and the public and private sectors (Colgan & McKearney, 2011;Humphrey, 1999). These studies reveal that the dynamics of the closet-selective/edited identity disclosureare common across many types of work and that different work cultures lead to different forms of exclusion, stereotyping, or workplace relationships.…”
Section: Work Cultures and Colleaguesmentioning
confidence: 99%
“…These stereotypes were only attached to positions outside of management, which demanded downplaying gay identities, contributing to a lavender ceiling. Wright (2011) interviewed lesbian women working in the U.K. construction industry and found that in a highly masculine environment, lesbians were actually better able to fit in, avoiding unwanted sexual attention and physical harassment experienced by heterosexual women (although a few reported harassment about their sexual identity).…”
Section: Work Cultures and Colleaguesmentioning
confidence: 99%
“…Lloren and Parini (2017) found that LGBT-supportive policies help to reduce discrimination based on sexual orientation. Qualitative study by Wright (2011) suggests that organizational response and practice is one of considerable factors that shape the realities of working lives for lesbians in traditionally male work. However, organizational policies alone are insufficient to protect gay and lesbian workers (Ragins et al , 2007).…”
Section: Introductionmentioning
confidence: 99%